The Impact of Motivation and Hygiene Factors on Research Performance: An Empirical Study from A Turkish University - Oya Tamtekin Aydın (International Review of Management and Marketing, 2012)
The purpose of this study is to find the differences of the effect of motivation factors and hygiene factors on research performance of Foundation University members in Turkey on the number of articles published in Science Citation Index and Social Science Citation Index. The study was conducted on 150 academics in a Turkish Foundation University. The following results are obtained from the study: i) The perception of academics on the effect of hygiene factors which include salary, job security, company policy-administration, supervision, interpersonal relations, status and working conditions on research performance is positive except status, ii) The perception of academics on the effect of motivators which include the possibility of growth, work itself, responsibility, achievement, advancement and recognition on research performance is positive.